Take Charge of Your Nursing Career, Second Edition. - Marshall, Lois Sarah (Indianapolis : Sigma, PPHU, Banecki, J., Jasniewski, I. i wspolnicy, spolka jawna, 2021)
Take Charge of Your Nursing Career, Second Edition provides nurses with a unique and distinct perspective to develop and manage their careers from beginning to end. With timely and relevant topics, strategies, tips, and examples, author, Lois Sarah Marshall helps nurses define their personal career trajectory no matter what point they are in their journey.
Front Cover -- Back Cover -- Endorsements -- Title Page -- Copyright Page -- Dedication -- Acknowledgments -- About the Author -- Contributing Authors -- Free Book Resources -- Table of Contents -- Foreword -- Preface -- Introduction -- Chapter 1: The Art and Science of Marketing Yourself -- Chapter 2: Your Career Repository: The Portfolio -- Chapter 3: Your Nursing Identity -- Chapter 4: Educational Advancement: Gaining New Expertise -- Chapter 5: Professional Development and Continuing Education: Role Expansion -- Chapter 6: The Value of Mentorship: A Two-Way Process to Pay It Forward -- Chapter 7: Career Development and Management for International Nurses -- Chapter 8: Using Social Media to Develop, Augment, and Propel Your Career -- Chapter 9: Expanding Your Reach: Using Your Voice -- Chapter 10: Entrepreneurship for the Professional Nurse -- Chapter 11: Work-Life Balance Issues: Managing Personal and Professional Time -- Appendix A: Examples of New and Experienced Nurse Resumes -- Appendix B: Curriculum Vitae -- Appendix C: Example of Blank CV -- Appendix D: Sample Cover Letters -- Appendix E: Personal Philosophy Example: Philosophy of Teaching -- Appendix F: Format for Developing Your Nursing Career Identity -- Appendix G: Mentoring Agreement -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Nursing--Vocational guidance; Career development; Electronic books